Pengembangan multimedia pembelajaran interaktif materi sistem organisasi kehidupan berbasis game edukasi - Miftakhul Huda; Munzil Munzil; Metri Dian Insani (Universitas Negeri Malang, 2021)
The aim of this research was to develop interactive learning multimedia in living organization system material on educational game. The validation test included media validation and material validation. The media validation was carried out by media expert, included of one physics lecturer and one natural science teacher, whereas the material validation was carried out by material expert, included of one biology lecturer. The legibility test in small group was carried out to 15 students grade VIII who had learned living organization system material. Based on the evaluation result, the developed interactive learning multimedia has proven valid and fulfilled very worthy criteria to be used. Penelitian ini bertujuan untuk menghasilkan multimedia pembelajaran interaktif pada materi sistem organisasi kehidupan berbasis game edukasi. Uji kelayakan dilakukan melalui validasi media, materi, dan uji keterbacaan. Validasi media oleh satu dosen Fisika dan satu guru IPA SMP, validasi materi oleh satu dosen biologi, dan uji keterbacaan pada 15 siswa kelas VIII SMP. Hasil penelitian menunjukkan bahwa multimedia yang dikembangkan sangat valid dan sangat layak untuk digunakan.